Regional Development Strategies for Major Cities - According to Economic Indicators - The Region of Aleppo’s Greater City as a Case Study: الاستراتيجيات التنموية لأقاليم المدن الكبرى - وفق المؤشرات الاقتصادية - حالة دراسية - إقليم مدينة حلب الكبرى - Heba Mohamad Kardosh, Abdulkader Abdulkarim Hariri (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
The aim of the study was to define some developmental concepts and discuss a variety of development theories that addressed economic development and its effect on the development and growth of the regions of major cities. The importance of the economic factor in the development process was emphasized in most development theories, by determining the most suitable investment locations and the best delivery of activities and services based on the best relationships. Afterwards, some Arab and international experiences were examined, which discussed the topic of research based on an analytical study of various economic considerations, and different scenarios were used to set development plans based on the priorities for achieving goals that differed by country. The study assumes that the lack of developmental balance between the city and its region is due to land use inconsistency and a lack of long-term planning for available resources and development potential. This resulted in the loss of many commercial and development prospects, a decline in agricultural output, and a rise in real estate rents in the surrounding areas of big cities in general, and Aleppo in particular. To track the problem, we used the historical method, the inductive method to read the facts, the deductive method to elicit the sources of the problem, the analytical method to analyze the causes, and the results were formulated using the analysis. Then, based on the strategies, theories, and experiences studied in the first topic, a development strategy was proposed based on the development indicators of the Greater Aleppo City region. To promote sustainable growth in the country, this strategy seeks to reduce development disparities throughout the region and achieve equity in the distribution of economic activity.